Perancangan Media Pembelajaran Interaktif Mata Pelajaran Tematik Bahasa Indonesia Untuk Siswa Kelas 1 Studi Kasus di SDN Leyangan - Daniel Rudjiono; Ester Dian Santoso (Pixel :Jurnal Ilmiah Komputer Grafis, 2023)
This Study aims to design interactive learning media in indonesian subjects, especially theme 2 sub-theme 4 lesson 5. Based on the identified students, that there are still students who are still not able to read and write fluently. This is due to factors from within the students themeselves such as the willingness and ability of the child. This type of research is a research and development research and development (R&D) method. This study uses six stages: (1) Potential and problems, (2) gathering information, (3) product design, (4) design validation, (5) design revision, (6) product trial, (7) product revision. Validation was carried out by media experts (lecturers) and material experts (teachers). The subjects of the research trial consisted of grade 1 students at SDN Leyangan. The trial was conducted by 5 students. Data collected by interviews, documentation, and questionnaires (questionnaires). The data are the results of an assessment of product quality and suggestions for revising the product, which are then analyzed descriptively. The results showed that interactive learning media for Indonesian thematic subjects as a media tool designed to be suitable for use in learning theme 2 sub-theme 4 lesson 5 class 1 SDN Leyangan. This is shown by (1) the assessment of the media expert (lecturer) included in the very good criteria with a score of 37, (2) the assessment of the material expert (teacher) included in the very good criteria with a score of 36, and (3) in the trial use included in the very good criteria with a score of 36.